Design como ferramenta de gestão estratégica nas micro e pequenas empresas: panorama da indústria moveleira em Bauru - SP - Wanderley, Denise Guimarães Guedes [UNESP] (2015)
Design has been highlighted as an important strategic management tool in business, able to improve processes and provide differential before the competition. The implementation of the design in the corporate environment, in order to make it part of the company culture is called Design Management. The economic scenario in Brazil points to, in the last decades, a strongly supported development in the growth of micro and small domestic companies. However, with high rates of closure, tools that help to strengthen the sector, such as design, can help to reverse this situation. In this context, this research sought to give an overview of the design in the economic micro-universe once it is an important link in strengthening the country's economy. The focus of the work stood on the micro and small furniture industries sector in the city of Bauru, SP. To conduct the survey, it was used the theoretical framework on the management of design and design for development. From there, it was elaborated a questionnaire based on the five factors usage design: awareness of the benefits, planning, resources, expertise and process, established in line with the Design Management Ladder, developed by the Design Management Europe. The questionnaire was applied to 29 industries, being considered valid responses from 26 companies. The data obtained allowed the classification of industries according to the Escada Management Design, as well as providing information for it to be traced the industry profile of the furniture industry in the city of Bauru. The results revealed that only 7.7% of the surveyed companies achieved the highest level in Ladder Management Design that design management is part of the company culture; 30.8% of companies are on the third level, where the design is used as a tool for innovation; in 42.3% the design is used... (Complete abstract electronic access below)